2023
DOI: 10.1177/15248380231190666
|View full text |Cite
|
Sign up to set email alerts
|

What Enables Child Sexual Abuse in Sport? A Systematic Review

Karl Dodd,
Colin Solomon,
Mitchell Naughton
et al.

Abstract: Sporting environments provide opportunities for perpetrators to commit child sexual abuse (CSA). While awareness of CSA in sport and preventative interventions are increasing, CSA in sport still occurs at alarming rates. A systematic review was conducted to identify and synthesize the extant literature on the enabling factors for CSA in sport. The 34 included articles were peer-reviewed and were primary sources; had full-text versions in English; included the individual, situational, environmental, or systemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…This disproportionate representation of factors in the system is a common observation across different domains of research, as evident in studies that have used systems thinking frameworks and methods. For example, studies have sought to identify what is known regarding barriers to treatment access for individuals with eating disorders (Lane et al, 2020), the factors that enable child sexual abuse in sport (Dodd et al, 2023), the factors that contribute to cycling incidents , and the factors influencing risk at rail level crossings (Read et al, 2021), have all concluded that more is known regarding the lower level factors.…”
Section: Facilitators and Barriers To Help-seeking For Self-harmmentioning
confidence: 99%
“…This disproportionate representation of factors in the system is a common observation across different domains of research, as evident in studies that have used systems thinking frameworks and methods. For example, studies have sought to identify what is known regarding barriers to treatment access for individuals with eating disorders (Lane et al, 2020), the factors that enable child sexual abuse in sport (Dodd et al, 2023), the factors that contribute to cycling incidents , and the factors influencing risk at rail level crossings (Read et al, 2021), have all concluded that more is known regarding the lower level factors.…”
Section: Facilitators and Barriers To Help-seeking For Self-harmmentioning
confidence: 99%
“…Another form of VAC which has prompted considerable attention within the scientific community is that of child sexual abuse (CSA). The numerous studies available show that CSA is present in diverse settings, including homes [6,7], schools [8,9], religious institutions [10], and broader communities [11]. The most prevalent context for children to encounter physical and emotional violence is typically within their own homes [12,13].…”
Section: Introductionmentioning
confidence: 99%